MODEL RANGSANG TANGGAPAN KONSUMEN MAHASISWA DI BENGKALIS - Yunelly Asra (Inovbiz: Jurnal Inovasi Bisnis, 2015)
Absract  :This  study  aims  to  determine  the  model  of  marketing  stimuli  for consumers teenagers, especially students in Bengkalis by the response they give the market encouragement that they received. Data collected in a non-probability sampling of 245 respondents with methods survey. Data collected through questionnaires  with  observational  techniques.  The  results  showed  that  the tendency of the responses given to the marketing stimuli is low. This is caused they are already accustomed to stimuli that exist today , they will be difficult to accept when there are new stimuli. Keywords: Marketing Stimuli, Consumer Response